Present methods of reconstruction of road bridges – examples of solutions - Śledziewski, Krzysztof (Budownictwo i Architektura / Civil and Architectural Engineering, 2012)
The article presents examples of contemporary methods of reconstruction of existing bridges. It describes the reconstruction of the bridge over the steel culvert and conversion of the bridge plate on the integrated bridge.